Los Frayles y sus Conventos (Llorens Hermanos Editores, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O Mestre d'Aviz : tragedia em quatro actos e a traducção das cinco primeiras elegias d'Albo Tibullo - Carvalho, José Manuel Teixeira de; Tibullus (Typ. Commercial, 1851)
Keywords: 18.Bookworm; 22.signature; 22.stamp; 28.Iron-gall ink; Condition: Fair; Hard Cover; USJ SEMINARY LIBRARY PROJECT

Historia General de la Iglesia - Castaneda, Diaz Iglesias (Imprenta de Ancos, Editor, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Reflexiones sobre La Naturaleza Escritas en Aleman - Cuchi, D. D. Tomas (Libreria Religiosa, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Reflexiones Sobre La Naturaleza Escritas en Aleman - D. D. Tomas Cuchi (Libreria Religiosa, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; Good

Instructions courtes et familières sur le symbole - Lambert, Joseph (Maison Méquignon Junior, 1851)
Keywords: 18.Bookworm (Only Cover); 2.Damage; Condition: Poor; Paperback; languages

Instructions courtes et familières sur le symbole - Lambert, Joseph (Maison Méquignon Junior, 1851)
Keywords: 2.Damage; Condition: Poor; Paperback; languages

Instructions courtes et familières sur le symbole - Lambert, Joseph (Maison Méquignon Junior, 1851)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Poor; Paperback; languages

instructions courtes et famieres sur le symbole - messire j. lambert (Méquignon-Junior, 1851)
Keywords: 10.Cover Damage; 13.Page missing; Condition: Poor; Hard Cover; languages

La Biblia Vulgata Latina - Miguel, Don Felipe Scio de San (Estabelcimiento Tipografico Editor, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

La Biblia Vulgata Latina - Miguel, Don Felipe Scio de San (Estabelcimiento Tipografico Editor, 1851)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Histoire du Consulat et de l'Empire: faisant suite à l'histoire de la Révolution française. Tome dixième - Thiers, Adolphe (Paulin, 1851)
Keywords: 18.Bookworm; 2.Damage; Condition: Poor; France 1804-1814 (Empire); Hard Cover; History

Histoire du Consulat et de l'Empire: faisant suite à l'histoire de la Révolution française. Tome onzième, [Février 1809 - Avril 1810] - Thiers, Adolphe (Paulin, 1851)
Keywords: 18.Bookworm; 2.Damage; Condition: Poor; France 1804-1814 (Empire); Hard Cover; History